Two-Weekly High-Dose-Rate Brachytherapy Boost After External Beam Radiotherapy for Localized Prostate Cancer: Long-Term Outcome and Toxicity Analysis - Tamihardja, Jörg; Lutyj, Paul; Kraft, Johannes; Lisowski, Dominik; Weick, Stefan; Flentje, Michael; Polat, Bülent (Frontiers in Oncology, 2021)
Purpose: Evaluation of clinical outcome of two-weekly high-dose-rate brachytherapy boost after external beam radiotherapy (EBRT) for localized prostate cancer. Methods: 338 patients with localized prostate cancer receiving definitive EBRT followed by a two-weekly high-dose-rate brachytherapy boost (HDR-BT boost) in the period of 2002 to 2019 were analyzed. EBRT, delivered in 46 Gy (DMean) in conventional fractionation, was followed by two fractions HDR-BT boost with 9 Gy (D90%) two and four weeks after EBRT. Androgen deprivation therapy (ADT) was added in 176 (52.1%) patients. Genitourinary (GU)/gastrointestinal (GI) toxicity was evaluated utilizing the Common Toxicity Criteria for Adverse Events (version 5.0) and biochemical failure was defined according to the Phoenix definition. Results: Median follow-up was 101.8 months. 15 (4.4%)/115 (34.0%)/208 (61.5%) patients had low-/ intermediate-/high-risk cancer according to the D`Amico risk classification. Estimated 5-year and 10-year biochemical relapse-free survival (bRFS) was 84.7% and 75.9% for all patients. The estimated 5-year bRFS was 93.3%, 93.4% and 79.5% for low-, intermediate- and high-risk disease, respectively. The estimated 10-year freedom from distant metastasis (FFM) and overall survival (OS) rates were 86.5% and 70.0%. Cumulative 5-year late GU toxicity and late GI toxicity grade ≥ 2 was observed in 19.3% and 5.0% of the patients, respectively. Cumulative 5-year late grade 3 GU/GI toxicity occurred in 3.6%/0.3%. Conclusions: Two-weekly HDR-BT boost after EBRT for localized prostate cancer showed an excellent toxicity profile with low GU/GI toxicity rates and effective long-term biochemical control.